Comparison between different boost dose delivery techniques to the tumor bed of right sided breast cancer patients. (JOURNAL OF ADVANCES IN PHYSICS, 2017)
Comparisons between three different techniques by which the boost dose was delivered to the tumor bed were carried out , aiming to present the best technique of treatment for right breast cancer patients. In this study, ten right sided breast cancer computed tomography (CT) scans were selected for ten early right breast cancer patients. We made three different treatment plans for each patient CT using three different irradiation techniques to deliver a prescribed boost dose of 10 Gy in 5 fractions to the boost PTV. In the first technique, two tangential photon beams were used, in the second technique we, two oblique photon beams were used and in the third technique, a single electron beam was used. The comparative analyses between the three techniques were performed by comparing the boost PTV- dose volume histograms (DVHs), the ipsilateral breast (right breast) DVHs, the ipsilateral lung (right lung) DVHs and the heart DVHs of the three techniques for each patient. Furthermore the dose that covering 100% , 95% of the volume (D100% , D95%) and the volume covered by 95% of the dose (V95%)of the boost PTV of all techniques, were calculated for each patient to investigate the dose coverage of the target. Results showed that there were variations of the dose received by tumor bed, right breast and OARs depending on the technique used and the target location and size. A decrease of D100% than 90% of the prescribed dose was observed with the 3rd technique for patients 8, 9 and 10, and was observed with the 2nd technique for patient 5. A reduction of right breast dose was observed when the 3rd technique was use in comparison with the 1st and the 2nd techniques for patients 1, 2, 3, 4, 6 and 8. Also reduction of right breast was observed when the 2nd technique used in comparison with 1st technique. An increase of lung dose was observed with the 3rd technique for patients 1, 2, 5 and 6, also was observed with 2nd technique in patient 3, 5 and 7. A decrease of lung dose was observed with the 1st technique for patients 2, 4, 5, 6, 7, 8 and 9 An individualized treatment, several plans using different irradiation techniques should be developed for each patient individually to reach the best boost PTV dose coverage with minimal OARs dose.